Chronopharmacology and controlled drug release - Lemmer, Björn (Expert opinion on drug delivery, 2005)
Circadian rhythms in the body are well established and are an important factor to consider when administering drugs. Many diseases display symptoms and onset characteristics that are not randomly distributed within 24 h (e.g., coronary infarction, angina pectoris, asthmatic attacks and peptic ulcer perforations); therefore, it is not surprising that the effects and/or pharmacokinetics of drugs can display significant daily variations. Recent data, primarily concerned with the chronopharmacokinetics of antiasthmatics, histamine H2-blockers and cardiovascular active drugs (e.g., propanolol, organic nitrate and nifedipine) are described as representative examples in this review. The data demonstrate that biological rhythms should have been taken into account when evaluating drug delivery systems, galenic formulations and pharmacokinetics as a basis for drug treatment.